(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluation of acute toxicity of Phellinus linteus biomass powder which obtained from submerged-fermentation in Institute of Biotechnology, VAST. Methods: Method for evaluation of drug toxicity, Medicinal Publishing House and OECD guidelines for testing of chemicals. Results and conclusions: The dose that did not cause abnormal symptoms observed in the trial was 18.0 g of sample / kg of mice. Lethal dose of 50% of experimental animals (LD50) was greater than 18.0 g of test sample / kg of mice. The results showed that mushroom biomass had low toxicity below the GHS classification threshold and did not cause toxicity to test animals.